INTERNATIONAL CONSENSUS PROJECT: NEURO-BEHCET DISEASE. Issue 10 (9th September 2014) - Kalra, Seema; Silman, Alan; Akman-Demir, Gulsen; Bohlega, Saeed; Bohrani-Haghighi, Afshin; Constantinescu, Cris; Houman, Habib; Mahr, Alfred; Salvarani, Carlos; Sfikakis, Petros P; Siva, A; Al-Araji, A
Abstract : Aim: Behçet's disease (BD) is a multisystem disease and neurological complications of Behçet's disease [neuro-Behçet's disease (NBD)] are amongst the life threatening and disabling manifestations. Evidence based is limited and there are no guidelines on the diagnostic and therapeutic aspects of NBD. We set out to develop clinical recommendations on the key issues in the diagnosis and management of NBD to assist clinicians involved in care of such patients. Methods: We performed a systematic literature search followed by a 4-round Delphi Consensus process. Literature search was performed using Cochrane, Medline and Embase databases with key words Behçet's*, Neuro-Behçet's* to include relevant published articles. After literature review draft recommendations were extracted and assessed with their level of evidence. Draft recommendations were reviewed by a group of 52 international experts from 22 countries and 11 medical specialities including neurologists, ophthalmologists, rheumatologists, internists, neuro-radiologist, neuro-pathologist, immunologist, dermatologist and paediatrician; and a patient representative. Draft recommendations were voted on by the consensus group and ones with high level of agreement (score ≥7/9) by ≥75% of the Group members were accepted as consensus recommendations (ICR). Results and Conclusions: International consensus project on Neuro-Behçet Disease has brought out ICR Diagnostic Criteria for NBD and recommendations on disease classification, diagnosis, role of investigations and management options in NBD. These will be presented at the meeting.